Single-machine scheduling with operator non-availability to minimize total weighted completion time - Wan, Long; Yuan, Jinjiang (Information sciences, 2018)
In this paper, we investigate the single-machine scheduling with an operator non-availability period to minimize total weighted completion time, where the operator non-availability period is an open time interval in which no job can be started or be completed. For this problem, we present a pseudo-polynomial-time algorithm and a fully polynomial-time approximation scheme. Our results address two open problems proposed in Chen et al. [2].